Developing an AR Navigation System: Bridging Indoor and Outdoor Environments - Achmad, Zacky Maulana; Sukaridhoto, Sritrusta; Zainuddin, Muhammad Agus (JOIV : International Journal on Informatics Visualization, 2025)
Navigation systems are designed to assist people or objects in moving efficiently and accurately from one place to another by providing directions to reach a destination. There are two main types of navigation systems: Indoor Navigation, which involves navigation within indoor environments, and Outdoor Navigation, which is used in outdoor or open environments. Both have drawbacks, such as signal limitations in multi-floor buildings and hardware requirements. This study focuses on developing a Seamless Indoor-Outdoor Navigation System that integrates indoor and outdoor navigation within a single application, allowing users to seamlessly transition between environments without switching applications or requiring additional hardware. The development uses AR technology and Immersal, overlaying digital content such as 3D pinpoints and 3D paths onto the real world through smartphones to show destinations to users. Immersal SDK adds real-world location mapping, application development, and localization for indoor and outdoor environments. The system was implemented at the PENS Campus, and testing was conducted, including: 1) Navigation Testing, which demonstrated efficient route visualization in the D3, D4, and S2 buildings and PENS Road. 2) User testing with the PIECES Framework, involving 35 respondents, showed high satisfaction with a top score of 4.49 for Information. 3) Indoor-outdoor integration Testing confirmed the system’s success in navigating between environments. 4) Multilevel Floor Navigation Testing demonstrated its ability to navigate multi-floor buildings, 5) Software Testing showed the system's performance met targeted frame rates of 30 FPS for Android and 60 FPS for iOS devices.